Boat noise and black drum vocalizations in Mar Chiquita coastal lagoon (Argentina) - Ceraulo, Maria (2021)
Human-generated underwater noise and its effect on marine biota is recognized as an important issue. Boat noise can affect the communication success of fish species that use sounds for spawning purposes. During the reproductive period, males of the black drum Pogonias spp. produce calls ranging from 90 Hz to 300 Hz. In the Mar Chiquita coastal lagoon (Buenos Aires, Argentina), Pogonias courbina is one of the primary fishing species. Although no regulation is directly applied to protect it, a ban protects the reproductive period of other fish species during weekdays. Here, we investigated the potential effect of boat noise on P. courbina vocalizations through a passive acoustic method. Acoustic data were collected, and P. courbina calls were identified and counted. The files with boat noise passages were categorized into classes according to their noise frequency range (A = below 700 Hz, B = over 700 Hz, and C = below and above 700 Hz). The fish call rate was lower in files where boat noise overlapped the fish call frequency (Classes A and C). Only boat noise from Class C was significantly reduced during days with the active fishing ban. These results suggest that anthropogenic noise may affect the P. courbina call rate and underline the importance of including the evaluation of anthropogenic noise in the current management of the area.